2008
DOI: 10.1007/s12349-008-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean food pattern: a good recipe for patients with the metabolic syndrome

Abstract: The metabolic syndrome is a complex condition characterized by dyslipidaemia, high blood pressure, impaired glucose tolerance and abdominal fat accumulation. Subjects with the metabolic syndrome are at high risk of atherosclerosis and coronary heart disease. A comprehensive approach is required for patients suffering this cluster of clinical manifestations. Indeed, subjects with the metabolic syndrome could benefit from life-style modifications, particularly through exercise and diet. In this article, the evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 136 publications
1
1
0
1
Order By: Relevance
“…Furthermore, unhealthy dietary habits such as skipping breakfast, frequent fast food intake and regular sweet consumption decreased the odds of being an olive oil consumer. Strong evidence support the notion that olive oil consumption is an integral key feature of the MD as it is the exclusive source of added fat [7,36,37]. In accordance with our results, a study among Greek adults reported that those consuming olive oil exclusively also reported higher consumption of legumes, fish, fruits and vegetables, reflecting a dietary pattern close to the MD [38].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, unhealthy dietary habits such as skipping breakfast, frequent fast food intake and regular sweet consumption decreased the odds of being an olive oil consumer. Strong evidence support the notion that olive oil consumption is an integral key feature of the MD as it is the exclusive source of added fat [7,36,37]. In accordance with our results, a study among Greek adults reported that those consuming olive oil exclusively also reported higher consumption of legumes, fish, fruits and vegetables, reflecting a dietary pattern close to the MD [38].…”
Section: Discussionsupporting
confidence: 91%
“…Así, el efecto beneficioso de la dieta mediterránea sobre los marcadores de estrés oxidativo está asociado, posiblemente, a la sinergia entre los macro y micronutrientes procedentes de alimentos que caracterizan este patrón dietético 45,46 . Los efectos favorables del consumo de la dieta mediterránea, durante 6 meses, se han hallado sobre los niveles plasmáticos de TBARS y actividad de la enzima GSH-Pox Tabla 5).…”
Section: Implicaciones Del Patrón Dietético Y De La Restricción Calórunclassified
“…When dietary fats are added, in accordance with the traditional Mediterranean diet, olive oil is the choice for children [ 17 ]. It has been repeatedly observed that individuals applying the Mediterranean diet have reduced risks of type 2 diabetes and other diseases associated with the metabolic syndrome, autoimmunological diseases, and certain forms of cancer [ 18 ]. Moreover, considerable evidence exists that the Mediterranean diet increases quality of life in the course of ageing, as well as longevity [ 13 , 19 ].…”
Section: Introductionmentioning
confidence: 99%